2000
DOI: 10.4049/jimmunol.165.5.2809
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement for Classic and Novel PKC Isoforms in Respiratory Burst and Phagocytosis in RAW 264.7 Cells

Abstract: The binding of Ab (IgG)-opsonized particles by FcγRs on macrophages results in phagocytosis of the particles and generation of a respiratory burst. Both IgG-stimulated phagocytosis and respiratory burst involve activation of protein kinase C (PKC). However, the specific PKC isoforms required for these responses have yet to be identified. We have studied the involvement of PKC isoforms in IgG-mediated phagocytosis and respiratory burst in the mouse macrophage-like cell line, RAW 264.7. Like primary monocyte/mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 44 publications
7
132
1
2
Order By: Relevance
“…Synchronized Phagocytosis and Immunofluorescence MicroscopyThe protocol for synchronized phagocytosis was adapted from Larsen et al (38). Briefly, macrophages plated in Plastek dishes and either infected or not with AdGFP-cPLA 2 ␣ were washed in cold HHBSS and cooled on ice for 5 min prior to addition of zymosan.…”
Section: Methodsmentioning
confidence: 99%
“…Synchronized Phagocytosis and Immunofluorescence MicroscopyThe protocol for synchronized phagocytosis was adapted from Larsen et al (38). Briefly, macrophages plated in Plastek dishes and either infected or not with AdGFP-cPLA 2 ␣ were washed in cold HHBSS and cooled on ice for 5 min prior to addition of zymosan.…”
Section: Methodsmentioning
confidence: 99%
“…For human monocytes and RAW264.7 macrophages, it has been shown that the primary event, that is, phosphorylation of p47 phox , is facilitated by protein kinase Ca (PKCa). 7,8 Recently, we demonstrated that downregulation of PKCa or expression of a kinase-dead mutant attenuates the PMA-induced oxidative burst. 9 However, the impact of AC on the oxidative burst remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Various PKC isoforms are recruited to forming phagosomes [49,50,66]. PKCε appears to regulate the rate of phagosome formation, as overexpression of PKCε increased rates of phagocytosis [50].…”
Section: Proteins Downstream Of the Fcr Complexmentioning
confidence: 99%
“…PLC hydrolyzes PI(4,5)P 2 to diacylglycerol and inositol trisphosphate, which can activate PKC and increase cytosolic-free calcium levels, respectively. Although increases in calcium are not necessary for phagocytosis by macrophages [88,89], local activation of PKC via diacylglycerol is important for phagosome formation [66] and activation of the NADPH oxidase complex [9]. PLA 2 , PLA-D 1 , and PLA-D 2 are also necessary for phagocytosis, perhaps because of their roles in membrane fusion reactions [46,68,69,90].…”
Section: Phagosomal Lipidsmentioning
confidence: 99%